Persistence and alteration of the song structure of the oriental Magpie Robin (Copsychus saularis) in some areas of Northern Thailand - Danmek A. (2017)
© 2017, Chiang Mai University. All rights reserved. In some areas of northern Thailand, the song heritage of the oriental magpie robin will either be maintained or change when transferred from adults to the next generation. The songs of birds in the breeding season of 2014 were compared to the songs of birds from the same study area in 2001. We found that the song frequency ranges, strophe structures, and song syntax patterns were not significantly different between the two years. This shows that the birds have maintained some form of the song structure over time for species recognition. In contrast, the mean strophe length, the number of elements per strophe, the mean length of the terminal part of the strophe, and the number of elements in the terminal part of the strophe were completely different between the two years. These results suggest that the influences of time and the song learning process have allowed theses birds to develop some form of their own song, resulting in song variation and unique song patterns.